Essential drugs in Bangladesh and role of different stake holders−a qualitative study - Akter, Seikh Farid Uddin; Rashid, Mohammad Abdur; Mazumder, Saroj Kumar; Jabbar, Md. Abdul; Sultana, Farhana; Rahman, Md Habibur; Shahrear Zahedee, Md Nasser (International Journal of Science, Environment and Technology, 2012)
In-depth interviews were conducted among 42 purposively selected participants to have an insight into the different issues pertaining to essential drugs such as access, availability, price fixation and update of the Essential Drugs List of Bangladesh. Their opinions seem to be divided as to the availability, production, relationships between price and availability, role of different stakeholders of essential drugs in general. But an unanimous opinion appears that the existing Essential Drugs List of Bangladesh is not enough comprehensive to serve the needs of people and demands at large. Therefore, this list should be updated with widely and wisely prescribed drugs based on scientific evidences.